1996
DOI: 10.1063/1.51403
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén waves, alpha particles, and pickup ions in the solar wind

Abstract: Past studies of the properties of Alfvtn waves in the solar wind have indicated that (1) the amplitude of the velocity 'fluctuations is almost always smaller than expected on the basis of the amplitude of the field fluctuations, even when the anisotropy of the plasma is taken into account, and (2) the alpha particles often do not participate in the wave motions because they "surf" on the waves carried by the proton fluid. Ulysses data are used to demonstrate that (1) the discrepancy between the velocity and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…But, candidates we have considered for mimicking outward-going Alfvdn waves seem problematic as explanations. If the reduced Alfv•n speeds as indicated by Goldstein et al [1995] are correct, then many of the points in Figure 2 Finally, we note that there is an important difference between the present results and the results of Marsch and Livi [1987]. We find from Ulysses that Vo/VA is almost always observed to be less than 2, and thus to statistically well satisfy the constraint corresponding to the instability threshold conditions.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…But, candidates we have considered for mimicking outward-going Alfvdn waves seem problematic as explanations. If the reduced Alfv•n speeds as indicated by Goldstein et al [1995] are correct, then many of the points in Figure 2 Finally, we note that there is an important difference between the present results and the results of Marsch and Livi [1987]. We find from Ulysses that Vo/VA is almost always observed to be less than 2, and thus to statistically well satisfy the constraint corresponding to the instability threshold conditions.…”
Section: Discussionsupporting
confidence: 59%
“…An additional issue is the actual propagation speed of Alfv•n waves in the solar wind: is it significantly modified by processes not in our theoretical model? Goldstein et al [1995] estimated that known sources (crosses in their Fig. 4) would reduce the Alfv•n speed by from 5 to 15% at high latitudes from 1.5 to 3 AU; the contribution of the two parallel proton beams is implicitly included in our theoretical calculation.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of all these arguments'we then propose that the large imbalance toward the magnetic energy found in the high-latitude interval is due to the inadequacy of the F = i assumption. In that region the presence of pickup ions has the effect of lowering F to values appreciably lesser than 1, in the line indicated by Goldstein et al [1995a], and hence of increasing the values of erR. The discrepancy of our result at high latitude can thus be canceled out.…”
Section: Thus Cvs Is Closer To 1 (In Absolute Value) As Closer a Poinsupporting
confidence: 45%
“…Finally, the high-latitude region (around 3 AU) offers a sample of turbulence typical of the polar solar wind. As shown by several studies (for instance, see Goldstein et al [1995a, hi, Hotbury et al [1995, and Smith et al [1995]), the polar turbulence appears significantly less evolved than that observed near the ecliptic.…”
mentioning
confidence: 85%
See 1 more Smart Citation